The impacts of diversified operations on lending of financial institution - Chiou, Jer-Shiou; Huang, Bor-Yi; Wu, Pei-Shan; Tsai, Chun-Ni (Journal of Business Economics and Management, 2012)
This study explores the impacts of bank’s diversified operations on their loans, the threshold effect of bank’s derivatives trading and the impacts on their financial behaviors are investigated. The results show that there are two separate regime effects for banks in large-sized and medium-sized, and three regime effects for banks in small to medium-sized. Derivatives trading not only make banks easier to diversify their credit risk exposure, but also alter their lending behaviors. As an example of large banks, when banks derivatives’ trading is more than US61 billion, an increase in banks assets will associate with a corresponding increase in loans to SMEs. If trading in derivatives by the banks is less than the threshold value, the banks will make loans less available to SMEs when there is an increase in banks assets. In addition, when banks are less aggressive in derivatives trading, debt ratio, pre-tax earnings and the SME credit guarantee balance all have significantly positive associations with loans to SMEs.